Optimizing the dose of upifitamab rilsodotin (UpRi; XMT-1536), a NaPi2b-directed dolaflexin antibody drug conjugate (ADC): A posthoc analysis of a phase 1b expansion study in ovarian cancer (319) - Monk, Bradley; Concin, Nicole; Richardson, Debra; Ray-Coquard, Isabelle; Pothuri, Bhavana; Marth, Christian; Bernardo, Patricia; Burger, Robert; Im, Ellie; Aldairy, Wassim; Coleman, Robert; Mirza, Mansoor (Gynecologic oncology, 2022)
Objectives: Effective and well-tolerated treatments for platinum- resistant ovarian cancer (PROC) remain a substantial unmet medical need. UpRi is a first-in-class Dolaflexin ADC targeting NaPi2b, a sodium-dependent phosphate transporter broadly expressed in high-grade serous epithelial ovarian cancer (OC), with limited expression in normal tissue. The purpose of this post-hoc analysis of data from the PhIb study is to determine if the dose of UpRi could be optimized in future studies to improve long-term tolerability and the therapeutic index. We evaluated the safety and overall response rate (ORR) in NaPi2b high and all evaluable patients (pts) based on various dose levels. Methods: The Ph1b PROC expansion cohort eligibility included pts with up to four prior lines of therapy. Pts were treated at either 36 or 43mg/m2 up to a maximum (max) dose of ~80mg for those patients with body surface area (BSA) ≥1.8m2, administered intravenously every four weeks. Tumor tissue was retrospectively evaluated for NaPi2b expression. An analysis was conducted on the expansion cohort to compare the efficacy and safety results of pts receiving doses ranging from 33-38mg/m2 (Group A, n=29) with those receiving >38mg/m2 (Group B, n=66). Group A included pts whose starting dose was 36mg/m2 (n=12) plus pts whose starting dose was ~80mg who received 33-38mg/m2 based on their BSA (n=17). Group B included pts in the 43mg/m2 group with BSA <1.8 (n=39) plus pts with BSA >1.8 but received >38mg/m2 (n=27). Two additional pts received <30mg/m2 and were not included in this analysis. Results: As of June 10, 2021, 97 pts were enrolled with a median age of 68 (33 to 87) years. The safety analysis included 95 pts: 29 in Group A and 66 in Group B. Dose reductions and discontinuations due to treatment-related adverse events (TRAEs) were lower in Group A (21% and 7%) than B (30% and 12%). Lower frequency of TRAEs was observed in Group A compared to B, 93% and 98%, respectively. The most common Grade >3 events included transient AST increase, fatigue, anemia, and thrombocytopenia; all were less frequent in Group A than B. No Grade 4 or 5 TRAEs were reported in Group A (See Table 1). Seventy-three pts were evaluable for response. The ORR was 36% (9/25) (95% CI: 18%-57%) in Group A and 23% (11/48) (95% CI: 12%-37%) in Group B. More responders were seen in high NaPi2b expressing tumors: ORR of 44% (7/16) (95% CI: 20%-70%) and 32% (7/22) (95% CI: 14%-55%) for Group A and B, respectively. Conclusions: In this post-hoc analysis of a phase Ib study comparing the safety and efficacy of UpRi in treating recurrent ovarian cancer, lower doses were associated with at least similar efficacy and improved tolerability than higher doses. These data support further clinical development of UpRi in the UPLIFT registrational study (NCT03319628), utilizing 36mg/m2 up to a max dose of approximately 80mg every four weeks.